The use of repetition suppression paradigms in developmental cognitive neuroscience. (July 2016) - Nordt, Marisa; Hoehl, Stefanie; Weigelt, Sarah
Abstract: Repetition suppression paradigms allow a more detailed look at brain functioning than classical paradigms and have been applied vigorously in adult cognitive neuroscience. These paradigms are well suited for studies in the field of developmental cognitive neuroscience as they can be applied without collecting a behavioral response and across all age groups. Furthermore, repetition suppression paradigms can be employed in various neuroscience techniques, such as functional magnetic resonance imaging (fMRI), functional near-infrared spectroscopy (fNIRS), electroencephalography (EEG) and magnetoencephalography (MEG). In the present article we review studies using repetition suppression paradigms in developmental cognitive neuroscience covering the age range from infancy to adolescence. Our first goal is to point out characteristics of developmental repetition suppression effects. In doing so, we discuss the relationship of the direction of repetition effects (suppression vs enhancement) with developmental factors, and address the question how the direction of repetition effects might be related to looking-time effects in behavioral infant paradigms, the most prominently used behavioral measure in infant research. To highlight the potential of repetition suppression paradigms, our second goal is to provide an overview on the insights recently obtained by applying repetition paradigms in neurodevelopmental studies, including research on children with autism spectrum disorders (ASDs). We conclude that repetition suppression paradigms are valuable tools for investigating neurodevelopmental processes, while at the same time we highlight the necessity for further studies that disentangle methodological and developmental factors.